Clinical epidemiology of Epstein-Barr virus-associated Lymphoproliferative Disorders (EBV-LPDs) in hospitalized children: A six-year multi-institutional study in China - Dilara Dilmurat; Xinyu Wang; Liwei Gao; Jiao Tian; Junhong Ai; Linlin Zhang; Mengjia Liu; Guoshuang Feng; Yueping Zeng; Ran Wang; Zhengde Xie (BMC, 2024)
Abstract Background Epstein-Barr virus-associated lymphoproliferative disorders (EBV-LPDs) are a group of disorders involving lymphoid tissues or lymphocytes. The epidemiology and economic burden of hospitalized children with EBV-LPDs in China have not been well studied. This study aimed to reveal the epidemic characteristics and disease burden of EBV-LPDs among the Chinese hospitalized children, providing strategies for the prevention and management. Methods This study was based on the FUTang Updating medical REcords (FUTURE) database of China and collected the medical records from 27 tertiary children's hospitals between January 2016 and December 2021 in China, counting five types of EBV-LPDs, namely EBV-positive T-cell lymphoproliferative disease, NK/T cell lymphoma, extranodal NK/T-cell lymphoma (nasal type), systemic EBV-positive T-cell lymphoproliferative disease of childhood and posttransplant lymphoproliferative disorders. We conducted a retrospective syhthesis and analysis of the epidemiological characteristics, expenses, length of stay (LOS), as well as complications among hospitalized children diagnosed with five types of EBV-LPDs and compared parameters using appropriate statistical tests. Results The study described 153 children aged 0-18 years hospitalized with EBV-LPDs from 2016 to 2021 in the FUTURE database. The male-to-female ratio was 1.10:1, and more than half of the age distribution was in the 6-12 y group. Among EBV-LPDs cases, EBV+ T-LPD accounted for the largest proportion (65.36%). Complications were presented in 93 children with EBV-LPDs, mainly hemophagocytic lymphohistiocytosis (HLH). The median LOS of NKTL was 26.5 days [interquartile range (IQR) = 3-42], which was the longest among EBV-LPDs. The median hospitalization cost of PTLD was 10 785.74 United States dollars (IQR = 7 329.38-16 531.18), which was the heaviest among EBV-LPDs. Conclusions Compared with the total number of hospitalized children in China during the same period and in the same age group, the proportion of EBV-LPD is very low. EBV-LPD can develop in all age groups, but it is more common in school-age children. Among 5 EBV-LPDs, the disease with the highest proportion is EBV+ T-LPD. The overall disease burden of EBV-LPD was heavy, especially the economic burden. HLH was one of the most common complications, which could directly affect the burden of patients because of prolonged hospitalization. These data are taken from a very large database, illustrating the epidemiological and economic burden of EBV-LPDs hospitalized children in China, which enriched the existing epidemiological and disease burden content of EBV-LPDs.